Phytochemical screening and antifungal potentials of Citrus limon peels against Fusarium oxysporum and Rhizopus stolonifer causing rots in water melon (Citrullus lanatus L.) - Bashir, L.U.; Abdulkadir, A.; Shah, M. M.; Hamisu, A.; Sharif, U.; Kamalu, A.A. (Journal of Experimental Sciences, 2020)
This study investigated the phytochemical constituents and antifungal potential of Citrus limon peels using aqueous and methanol extracts against Fusarium oxysporum and Rhizopus stolonifer causing rots in water melon. The result of phytocemical screening revealed the presence of Saponin, Tannin, Phenols, Alkaloid and Flavanoid. Pathogenicity test conducted showed that F. oxysporum and R. stolonifer causes rots of Citrullus lanatus. The extracts inhibited the growth of F. oxysporum (76.67% and 60.00 %) methanol and aqueous respectively. R. stolonifer growth was inhibited (85.93% and 71.11%) methanol and aqueous extracts. The fungitoxicity of synthetic fungicide Benomyl was 95.56%. The methanol extracts has highest inhibitory activity than aqueous extract. The result of the findings indicates the Biofungicide potentials of Citrus limon peels as alternative to synthetic fungicide in management of phyto-pathogens of water lemon.